A critical analysis of the crisis of Islamic education in Malaysia - Hussien, Suhailah (IIUM Press, International Islamic University Malaysia, 2011)
The purpose of this chapter is to reveal how the influence of western modernity has created a crisis in Islamic education in Malaysia in at least two related aspects. The first is the ‘crisis of secularisation’, created by a dualistic curriculum of education in Malaysia; in the Islamic religious schools and the National schools. The second is the ‘crisis of modernisation’ created by the impact of western science and technology on both of these Malaysian educational systems. In analysing this crisis, this chapter is organised into three sections. The first section defines ‘crisis’, explores what it is all about, analyses the Malaysian government’s attempt to resolve it, and how the government’s effort have simply exacerbated the ‘crisis’. The second section examines some Muslim scholars’ response to this crisis, how this led to the birth of the project of ‘Islamisation of Knowledge’, its aims, implementation and problems. Finally, in the third section I provide a critical analysis of the Islamisation of Knowledge’s epistemology and methodology.